The Immediate and Sustained Effects of Moderate-Intensity Continuous Exercise and High-Intensity Interval Exercise on Working Memory - Mou, Hong; Tian, Shudong; Fang, Qun; Qiu, Fanghui (Frontiers in Psychology, 2022)
This study investigated the immediate and delayed effects of moderate-intensity continuous exercise (MICE) and high-intensity interval exercise (HIIE) on working memory. Fifty healthy young adults (mean age = 19.96 ± 1.03 years) engaged in (1) a MICE session, 20 min of continuous running on a treadmill at an intensity of 40-59% of heart rate reserve (HRR); (2) a HIIE session, ten sets of 1 min running at an intensity of 90% HRR, interspersed by 1 min self-paced walking at 50% HRR; and (3) a control session, resting in a chair and reading books for 24 min. A spatial 2-back task was per-formed to assess working memory before, immediately after and 30 min after each intervention. Reaction time in the 2-back task was significantly reduced immediately after both MICE and HIIE interventions. The enhanced working memory associated with HIIE sustained for 30 min after the exercise, whereas the beneficial effects associated with MICE returned to the pre-exercise level at 30 min after the exercise. These results suggest that although both MICE and HIIE enhance working memory in young adults, the positive effect sustains longer in HIIE than that in MICE. The current study extends the existing knowledge base by suggesting that improvements in working memory with HIIE last longer than with MICE.